Do intersecting identities structure social contexts to influence life course health? The case of school peer economic disadvantage and obesity. (November 2021) - Polos, Jessica; Koning, Stephanie; McDade, Thomas
Abstract: Scholarship linking social contextual measures to health outcomes has grown in recent decades, but the role of individuals' intersecting identities in structuring social contexts to influence health remains unclear. Building on an existing intersectionality framework, we conceptualize how this may occur through social relationships. Then, we apply this framework to analyze whether adolescent peer social contextual disadvantage influences life-course obesity heterogeneously by individual gender, race, and early-life income. We take a life course approach as adolescence is a sensitive period for both social development and adult obesity development. In our analysis, we use cohort data from the National Longitudinal Study of Adolescent to Adult Health and leverage quasi-experimental variation in adolescent peers to addresses common sources of bias in prior observational studies. We find that among Black men from lower-income households in adolescence, there is a strong negative relationship between adolescent peer economic disadvantage and adult obesity that strengthens over time. By contrast, among Black women across adolescent household income levels, we find a strong positive relationship between adolescent peer economic disadvantage and obesity that emerges as women leave high school and endures into mid-adulthood. Among non-Black women, a more modest positive relationship appears between peer disadvantage and obesity. Among non-Black men, we find no relationship. These diverging patterns suggest that the pathways through which adolescent peer economic disadvantage influences health may differ or produce differential effects based on intersecting race, gender, and socioeconomic identities. Such heterogenous effects offer new insights, and future directions, for better understanding social life-course determinants of adult health and addressing inequities. Highlights: Social contexts are comprised of social relationships and matter for health. Intersecting identities (race/SES/gender) structure relationships in contexts. The relationship between social context and health differs by individual identities. The study quasi-experimentally measures adolescent peer economic contexts. Peer disadvantage impacts life course obesity differently by individual identities.